Development of Storytelling-Based Hand Puppet Media to Enhance Narrative Text Comprehension among Third-Grade Elementary Students - Cahyani, Bella Galih; Sismulyasih SB, Nugraheti (Jurnal Paedagogy, 2026)
This study aims to develop storytelling-based hand puppets to improve the reading comprehension skills of third-grade elementary school students. The research employed a Research and Development (R&D) method involving third-grade students at SD Negeri 2 Kuwu as the research participants. The study also involved teachers, students, and expert validators in media and learning materials. Data were collected through observations, interviews, tests, and questionnaires, and were analyzed using both descriptive qualitative and quantitative methods. The effectiveness of the developed media was evaluated by comparing students’ pre-test and post-test scores using N-gain analysis. The validation results indicated a very high level of feasibility, with scores of 94% from media experts and 90.90% from material experts. Student responses reached 91.11%, while teacher responses were 100%, all of which were categorized as very good. The t-test results showed a significance value of < 0.001, indicating a statistically significant difference between pre-test and post-test scores. Furthermore, the N-gain analysis revealed an increase in the average scores from 70.24 to 89.63, with an N-gain value of 0.65, which falls into the moderate category. In conclusion, the storytelling-based hand puppets are valid, practical, and effective for use in learning. The developed media have been proven to positively influence the narrative text comprehension skills of third-grade students at SD Negeri 2 Kuwu.